Antecedent of Knowledge, Awareness and Willingness of SMEs Actors to Register for Halal Self Declare Certification - Cahyaning B Utami; Faiqul Hazmi; Rizka Aulia; Binti M Zahro (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2022)
Consuming halal products has become a lifestyle and trend for both Muslim and non-Muslim communities throughout the world. Despite creating a large market potential and the government has strong desire to make Indonesia as a reference for world halal producers and encourage the facilitation of knowledge and awareness of halal products. This study aims to determine the effect of the knowledge of SMEs actors about halal certification on willingness to take halal certification and find out whether awareness of halal products has an influence on willingness to take halal certification. This study used a questionnaire in data collection, and the research informants were micro and small business actors in the food and beverage sector. The results of this study found that knowledge has no significant effect on the willingness of SMEs to participate in self-declared halal certification, while awareness has a positive and significant effect on the willingness of SMEs to participate in self-declare halal certification. The implications of this finding can be conveyed to the government in order to conduct intensive socialization regarding free halal certification which can involve micro and small actors who are successful in participating of halal certification.